Burning mouth syndrome – a common dental problem in perimenopausal women - Ślebioda, Zuzanna; Szponar, Elżbieta (Menopause Review/Przegląd Menopauzalny, 2014)
Burning mouth syndrome (BMS) is characterized by the presence of burning, paresthesia or pain of the oral mucosa in the absence of pathologic lesions revealed during the clinical examination [1-3]. Moreover, the pain may be accompanied by oral dryness, hypersensitivity to some food compounds and taste disorders [4-6]. Etiopathogenesis of this condition remains unclear. Potential local causative factors include among the others mechanical irritation, parafunctions and dysfunctions of the stomatognathic system, contact allergy to dental materials and electro-galvanic phenomena. Potential systemic causes include diabetes mellitus, B group vitamin deficiency (vitamins B1, B2, B6 and B12), folic acid and iron deficiency, hormonal imbalance, gastrointestinal diseases, psychiatric and neurological disorders and drug-induced side effects. The hypothesis concerning the role of hormonal changes in the development of BMS seems to be confirmed by a high incidence of this condition in perimenopausal women [2, 7, 8]. Up to now, due to an unclear etiology of the disease, the treatment is very often ineffective and mainly symptomatic, which may exacerbate patient’s anxiety and discomfort. In this paper we present the main etiologic factors of the burning mouth syndrome. We discuss the basic diagnostic and therapeutic methods and the influence of hormonal replacement therapy on the course of BMS based on the current medical reports.